Ag(I)-Mediated Oxidative Radical Triﬂuoromethylthiolation of Alkenes - Zheng, Changge; Liu, Yang; Hong, Jianquan; Huang, Shuai; Zhang, Wei; Yang, Yupeng; Fang, Ge (Synlett, 2019)
A simple, mild, and efficient method for an oxidative radical triﬂuoromethylthiolation of alkenes through AgSCF3/K2S2O8 system has been developed. This reaction provides a straightforward way to synthesize a variety of useful α-SCF3-substituted ketone compounds from a wide range of alkenes in moderate to good yields.
Keywords: triﬂuoromethylthiolation; alkenes; AgSCF3; α-SCF3-substituted ketone; radical pathway